Comparison of thoracic computed tomography and surgical reports in dogs and cats - Brložnik, Maja; Immler, Martin; Prüllage, Maria Laura; Grünzweil, Olivia Mariel; Lyrakis, Manolis; Ludewig, Eberhard; Kneissl, Sibylle Maria (Frontiers in Veterinary Science, 2025)
IntroductionThis retrospective study compared computed tomography (CT) and surgical reports in 41 dogs and 23 cats undergoing thoracic surgery (50 thoracotomies, 14 thoracoscopies).ObjectivesThe objective of this study was to evaluate the agreement between imaging and surgical findings in dogs and cats undergoing thoracic surgery and to access sensitivity of imaging for major surgical finding.MethodsPatients were included if they had an in-house CT study performed within 8 days prior to surgery, had a finalized CT report available before surgery, and if the corresponding surgical report was sufficiently detailed to allow meaningful comparison with CT findings. Imaging and surgical findings were extracted and categorized as complete agreement, partial agreement (regarding type, number, or site of lesion), no agreement, or equivocal. Short-term outcome (discharged or deceased) was recorded.ResultsAgreement between primary imaging and surgical findings was achieved in 55 of 64 patients (86%): 33 dogs (33/41; 80%) and 22 cats (22/23; 96%). No agreement was found in 6 of 64 patients (9%): bullae were not detected in 3 dogs and 1 cat, a foreign body was missed in 1 dog, and pericarditis was missed in 1 dog. Partial agreement was found in one patient with several bullae (2%). Based on the available data, 2 of 64 patients could not be classified (3%). Surgical reports documented that the most common lesions were pleural effusion (12 dogs, 15 cats) and pulmonary mass/nodule (14 dogs, 5 cats). Fifty-two patients were discharged, while twelve (12/64; 19%) died before discharge (six patients died and six were euthanized). Significant association between categories of pathology and agreement was observed (p < 0.001). The categories of pathology with the highest number of cases (lung mass (n = 19) and pleural effusion (n = 27)) showed only complete agreement between primary imaging and surgical findings. Differences in agreement were associated with perception (n = 4), cognitive error (n = 2) and discrepancy (n = 1).ConclusionSmall and camouflaged pathologies, such as low-contrast foreign bodies and ruptured bullae in the atelectatic lung, were most frequently missed or wrongly interpreted in CT reports.